Hukum Bermain Catur Menurut Mazhab Syafi’i dan Mazhab Maliki - Muiz, Moch. Zulkarnain (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2021)
Abstract: This article discusses the laws of playing chess according to the Syafi'i and Maliki schools. This research is library research and qualitative. Data were collected through the books of the mazhab Syafi'i and Maliki scholars, then the collected data were analyzed descriptively comparatively. The Syafi'i school argues that the law of playing chess is makruh as long as it is not accompanied by gambling, dirty speech, and obligatory worship. The Maliki school argues that playing chess is haram because it is similar to dice. Based on the comparative analysis, the Syafi'i school and the Maliki school agree that it is forbidden to play chess if it is accompanied by gambling and if it causes dirty speech and neglects obligatory worship. The two schools differ in their opinion regarding the law of playing chess that the Syafi'i mazhab requires playing chess based on the fiqh rule